Liudmyla Kulieshova: PRAGMATIC TYPES OF ADVERTISING SLOGANS IN THE INTERNET - Kulieshova, Liudmyla (Linguistic Bulletin (Movoznavchyi Visnyk), 2022)
Аbstract. Introduction. Internet advertising is one of the most popular speech genres today. In the study of the linguistic aspect of advertising, advertising slogans occupy a leading place. Like any speech activity, they have a pragmatic aspect, that is, they express the attitude of the speaker to the recipient, they realize a certain communicative goal. It turned out that in order to characterize the pragmatic content of advertising slogans, it is convenient to use the commonly used classification of speech acts. Purpose. The objective of the paper is to identify the types of advertising slogans used in Internet advertising, based on the classification of speech acts, and to characterize their features. Results. As the study shows, several types of speech acts are the most common in advertising slogans. Assertive slogans are aimed at the consent of the recipient with what is being affirmed through the expression of some fact. The most frequent are directive slogans, the task of which is to encourage the consumer to make a decision to purchase the advertised product or service. Direct and immediate, categorical motivation is expressed by slogans-appeals. Less categorical are such varieties of directive slogans as offer and advice. The communicative goal of expressive slogans is a positive reaction of the recipient to the emotional state expressed in the slogan associated with the object of advertising. As the analysis of advertising texts shows, interrogatives are used in the slogans of Internet advertising – questions, the answers to which imply a positive attitude towards the objects of advertising. Another pragmatic type of statements in advertising slogans is commissions, i. e. promises that inspire confidence in the positive nature of what is being advertised. Conclusion. The research which has been made provides grounds for the conclusion that advertising slogans on the Internet represent a type of speech activity. It turned out that in order to characterize the pragmatic content of advertising slogans, it is convenient to use the commonly adopted classification of speech acts. At the same time, as the analysis of the available materials has shown, the texts of advertising slogans on the Internet can be pragmatically attributed to assertives, directives, expressives and commissions.